Human mAbs to Staphylococcus aureus IsdA Provide Protection Through Both Heme-Blocking and Fc-Mediated Mechanisms. (29th November 2018) - Bennett, Monique R; Bombardi, Robin G; Kose, Nurgun; Parrish, Erica H; Nagel, Marcus B; Petit, Robert A; Read, Timothy D; Schey, Kevin L; Thomsen, Isaac P; Skaar, Eric P; Crowe, James E
Abstract: The nutrient metal iron plays a key role in the survival of microorganisms. The iron-regulated surface determinant (Isd) system scavenges heme-iron from the human host, enabling acquisition of iron in iron-deplete conditions in Staphylococcus aureus during infection. The cell surface receptors IsdB and IsdH bind hemoproteins and transfer heme to IsdA, the final surface protein before heme-iron is transported through the peptidoglycan. To define the human B-cell response to IsdA, we isolated human monoclonal antibodies (mAbs) specific to the surface Isd proteins and determined their mechanism of action. We describe the first isolation of fully human IsdA and IsdH mAbs, as well as cross-reactive Isd mAbs. Two of the identified IsdA mAbs worked in a murine septic model of infection to reduce bacterial burden during staphylococcal infection. Their protection was a result of both heme-blocking and Fc-mediated effector functions, underscoring the importance of targeting S. aure us using diverse mechanisms. Abstract : The human pathogen Staphylococcus aureus causes a wide range of infections, but there is currently no licensed vaccine to prevent infection. This study shows anti-Isd antibodies can decrease bacterial burden by blocking heme acquisition and by mediating Fc-mediated mechanisms.